Clinical and molecular findings in IPEX syndrome. Issue 1 (20th December 2005) - Myers, A K; Perroni, L; Costigan, C; Reardon, W
Abstract : IPEX (immunodysregulation, polyendocrinopathy, enteropathy, X linked syndrome) is a rare disorder which usually results in death in early infancy or childhood. Clinical awareness remains the cornerstone of diagnosis, and provided that the diagnosis is entertained, mutation analysis for FOXP3 gene mutations can be confirmatory. Two new patients in whom IPEX was diagnosed retrospectively are reported.